2018
DOI: 10.21147/j.issn.1000-9604.2018.02.08
|View full text |Cite
|
Sign up to set email alerts
|

Elevated preoperative plasma D-dimer dose not adversely affect survival of gastric cancer after gastrectomy with curative intent: A propensity score analysis

Abstract: The poor prognosis of GC patients with elevated preoperative PDL was due to the advanced tumor stage and elder age rather than the elevated D-dimer itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Long Liu et al reported that high D-dimer level may predict poor outcome of GC patients 14 . Controversially, Yuexiang Liang et al illuminated that preoperative D-dimer was not an independent prognostic factor for patients with GC after curative resection 18 . Although the difference in research results may be due to regional differences in distribution and the influence of confounding factors, it is significant to explore the prognostic value of D-dimer in GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long Liu et al reported that high D-dimer level may predict poor outcome of GC patients 14 . Controversially, Yuexiang Liang et al illuminated that preoperative D-dimer was not an independent prognostic factor for patients with GC after curative resection 18 . Although the difference in research results may be due to regional differences in distribution and the influence of confounding factors, it is significant to explore the prognostic value of D-dimer in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our previous research showed that D-dimer is not only an indicator of venous thrombosis but also a marker for predicting cancer progression in GC patients 17 . In contrast, Liang et al reported that elevated preoperative D-dimer was not an independent prognostic factor for GC based on propensity score matching analysis 18 . Based on this controversy, the aim of our study was to explore the correlation between preoperative D-dimer and long-term survival of GC patients after curative surgery.…”
Section: Introductionmentioning
confidence: 95%
“…D-dimer is one of the terminal fibrin decomposition products, which can affect cellular signaling systems, promote cell proliferation, stimulate cellular adhesion of tumor cells to endothelial cells and affect platelets and extra-cellular matrix, inducing the growth and spread of tumors 4. In a study of 41 gastric cancer patients, Dian analyzed the plasma D-dimer levels and circulating tumor cells, concluded that D-dimer was an essential accompaniment of circulating tumor cells in gastric cancer, which can be used in the detection of hematogenous metastasis 5.…”
Section: Introductionmentioning
confidence: 99%